Toward a participatory approach in the implementation of AI in Colombian Universities: analysis of protocols and proposals for knowledge production - Ospina-Deaza, Juan Camilo (2026)
This article examines the development and implementation of artificial intelligence (AI) protocols in Colombian universities, within a context marked by the digital divide and educational challenges. Using a grounded theory approach, eleven institutional documents published between 2023 and 2025 were analyzed, identifying key themes such as ethical responsibility, transparency, data protection, and equitable access. The protocols reveal divergences in the definition of AI, ranging from functional to critical and humanistic approaches. However, significant omissions are observed, including the lack of risk assessment frameworks and the exclusion of diverse actors from the educational community. The creation of AI protocols in academic contexts implies rethinking how knowledge is constructed, validated, and shared. While AI can transform teaching, research, and management processes, it also poses risks such as the dehumanization of learning, the perpetuation of algorithmic biases, and the exclusion of marginalized communities. This study proposes a roadmap for updating and creating new protocols, integrating participatory and interdisciplinary approaches to ensure the inclusion of diverse voices and a comprehensive understanding of the AI lifecycle, beyond the use of generative models.